Effects of Urban and Rural Resident Basic Medical Insurance on Healthcare Utilization Inequality in China - Liangwen Zhang; Rui Chen; Ya Fang (Frontiers Media S.A., 2023)
Objectives: This study aims to evaluate the effects of Urban and Rural Resident Basic Medical Insurance (URRBMI) integration on healthcare utilization and explore the contribution of URRBMI to healthcare utilization inequality among middle-aged and older adults.Methods: Using data from the China Health and Retirement Longitudinal Study (CHARLS) 2011-2018. The difference-in-difference model, concentration index (CI), and decomposition method were adopted.Results: The results suggested that the probability of outpatient visits and the number of outpatient visits had decreased by 18.2% and 10.0% respectively, and the number of inpatient visits had increased by 3.6%. However, URRBMI had an insignificant effect on the probability of inpatient visits. A pro-poor inequality for the treatment group was observed. The decomposition revealed that the URRBMI contributed to the pro-poor inequality in healthcare utilization.Conclusion: The findings suggest that URRBMI integration has decreased outpatient care utilization and improved the number of inpatient visits. While the URRBMI has improved healthcare utilization inequality, some challenges still exist. Comprehensive measures should be taken in the future.